Relaciones entre esquemas de demostración de teoremas y resolución de problemas. avances en la caracterización del pensamiento algebraico - Penagos, Mauricio (Universidad Antonio Nariño, 2021)
Advances are presented in the characterization of algebraic thinking, when performing an investigation with a group of twelve undergraduate students in Mathematics of an Algebraic Structures course, if there are relationships between two activities own of mathematics: solve problems and prove theorems.